Morphophysiological Response of Peranggi Chili (Capsicum annum L. var chinensis) to Drought Stress (International Journal of Scientific Research and Management (IJSRM), 2024)
Peranggi chili (Capsicum annum L. var chinensis) is a red chili that has a spicy taste. Peranggi chili is not widely known by the community and has not been widely studied. In addition, peranggi chili is very easily exposed to drought so its growth is easily disrupted. This study aimed to determine morphophysiology of peranggi chili with PEG treatment as drought stress with concentrations of 0%, 10%, 20%, and 30%. This research was conducted from June to November 2024. The study used an experimental method with a completely randomized design (CRD) to test the growth of peranggi chili with PEG 6000 treatment as drought stress with concentrations of 0%, 10%, 20%, and 30%. The treatment was given after the chili grew 30 days after transfer (DAT). Measurements were taken at 40, 50, 60, and 70 DAT. The results showed that the morphology of peranggi chili plants was not affected by different concentrations of PEG 6000 except root length which decreased significantly at 70 DAT. The shoot: root fresh and dry weight ratio decreased until 50 DAT and reduce slowly until 70 DAT. Similarly, physiological measurements in the form of chlorophyll a, b, and total content decreased from 50 to 70 DAT, but the treatment level had a different impact. From this study, the effect of drought stress using PEG 6000 0%, 10%, 20%, and 30% began to affect the vegetative growth of peranggi chili peppers at 50 DAT.